Sistema de egressos UFPA - Campus Castanhal - RODRIGUES, Felipe Moraes (2022)
In this End of Course Work, the knowledge acquired during this academic formation was used for the development of a system of egresses to the Federal University of Pará (UFPA), university campus of Castanhal, seeking to strengthen the relationship between former students, the institution and the labor market, in view that this interaction is usually impaired due to the loss of link with the university, being also a reality in most HEIs (Higher Education Institutions). Thus, this system will be a source of essential information for the institution's educational management and will help its graduates to enter the job market, implying directly and indirectly in its success. It was used in its development Software Engineering resources for system modeling, the use of project standards, and a set of very useful tools for building modern systems.